A Mathematical Model for Ethanol Fermentation From Oil Palm Trunk Sap Using Saccharomyces Cerevisiae - Sultana, Sharmin; Norazaliza, Jamil; Saleh, E. A. M.; Yousuf, Abu; C. K. M., Faizal (IOP Publishing, 2017)
This paper presents a mathematical model and solution strategy of ethanol fermentation for oil palm trunk (OPT) sap by considering the effect of substrate limitation, substrate inhibition product inhibition and cell death. To investigate the effect of cell death rate on the fermentation process we extended and improved the current mathematical model. The kinetic parameters of the model were determined by nonlinear regression using maximum likelihood function. The temporal profiles of sugar, cell and ethanol concentrations were modelled by a set of ordinary differential equations, which were solved numerically by the 4th order Runge-Kutta method. The model was validated by the experimental data and the agreement between the model and experimental results demonstrates that the model is reasonable for prediction of the dynamic behaviour of the fermentation process.